HARDENING AS THE BASIS OF A HEALTHY LIFESTYLE IN PRESCHOOL CHILDREN (Conferencea, 2023)
The article is devoted to the urgent problem of comprehensive development of physical and psychological health of preschool children; hardening of the body by natural forces of nature.